Model Pembelajaran Cooperative Learning Tipe Jigsaw Dan Minat Belajar Dalam Peningkatan Hasil Belajar Siswa - Resnawita, Resnawita; Fatimah, Siti; Nurdin, Buchari (RC-INSTITUT, 2018)
This  thesis  discusses  about  the  Influence  of  Cooperative  Learning Model of Jigsaw Type Learning and Interest Learning on Student Learning Outcomes in SMA Negeri 1 Sutera. The formulation of the problem in this research are: (1) where the learning result of the students who are taught with Jigsaw type cooperative learning model is better than the students' learning result which is taught by conventional learning, (2) where is the result of student learning  with  high  interest  in  Jigsaw  class  higher  than  student  learning outcomes with high interest in conventional class, (3) whether student learning outcomes with low interest in Jigsaw classes is higher than student learning outcomes with low interest in the conventional class. The research method used in the writing of the thesis in accordance with the type of research is quasi experimental research (quasi experimental), where the research variables can not be fully controlled. This type of research has a control group. The research design used to measure the learning method and the students' learning interest toward the learning outcomes on the dissemination of culture and religion in this research is the pattern of care by the level (2x2), with the state of each student learning interest level.From result of research revealed (1) result of student learning taught by approach of learning model of Cooperative Learning Jigsaw type better compare to result of student learning taught by conventional approach, (2) result of student learning having high learning interest taught by learning model of learning Jigsaw type cooperative is better than the result of study of students who have high interest in the class taught by conventional approach, (3) the learning result of students who have low learning interest taught by the model of learning Jigsaw type cooperative learning is better than student learning outcomes that have low interest in classes taught by conventional approaches.